2022
DOI: 10.3390/socsci12010013
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the Sustainability-Oriented Entrepreneurship Intentions of Business School Students: The Role of Individualistic Values

Abstract: This study sought to determine whether Ajzen’s theory of planned behaviour could be used to predict the intention of selected Zimbabwean business school students towards sustainable entrepreneurship. The study also examined whether the relationships between the predictor variables of the theory of planned behaviour and sustainable entrepreneurial intention were moderated by the respondents’ individualistic value orientations. A positivist worldview and a quantitative cross-sectional survey were used to collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 66 publications
1
4
0
1
Order By: Relevance
“…The impact of subjective norms on sustainable entrepreneurial intention was indirect, and the effect was completely mediated by the attitude towards behavior. Individualistic values did not moderate the connections between the predictors of intention and the intention to engage in sustainable entrepreneurship in a statistically meaningful way (Ndofirepi, 2022). Certain personal characteristics can serve as predictors for promoting new ventures.…”
Section: Literature Reviewmentioning
confidence: 69%
“…The impact of subjective norms on sustainable entrepreneurial intention was indirect, and the effect was completely mediated by the attitude towards behavior. Individualistic values did not moderate the connections between the predictors of intention and the intention to engage in sustainable entrepreneurship in a statistically meaningful way (Ndofirepi, 2022). Certain personal characteristics can serve as predictors for promoting new ventures.…”
Section: Literature Reviewmentioning
confidence: 69%
“…The intention is shaped by three primary determinants: the individual's disposition towards the behavior, subjective norms, and perceived behavioral control. A study by (Ndofirepi, 2023) revealed that the variable of attitude toward behavior had a statistically significant direct impact on sustainable entrepreneurial intention, which was mediated by attitude towards behavior. Subsequent analysis revealed that subjective norms are one of the three components of the Theory of Planned Behavior (TPB).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Dalam konteks ini, studentpreneurship merupakan program kewirausahaan yang diberikan kepada peserta didik untuk memunculkan ide-ide yang berbeda dari perspektif yang beragam untuk memecahkan masalah. Ketika mereka lulus, mereka akan mampu menciptakan hal-hal baru dan berani mengambil risiko, berinovasi, dan keluar dari zona nyaman dalam pekerjaan dan bisnis mereka (Lackéus, 2015;Suacamram, 2019;Lilischkis et al, 2021;Ndofirepi, 2023). Untuk menumbuhkan jiwa dan kemampuan kewirausahaan, seorang perlu berpartisipasi dalam proses pengembangan kewirausahaan melalui pengalamannya sendiri.…”
Section: Pendahuluanunclassified